2019
DOI: 10.3382/ps/pez375
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of 2 phytases on inositol phosphate degradation in different segments of the gastrointestinal tract, calcium and phosphorus digestibility, and bone quality of broilers

Abstract: The anti-nutritional effects of dietary inositol phosphates (IP6 through IP3) have been recognized in broiler chickens; however, inositol hexaphosphate (IP6) is more potent than the lower IP esters. The efficacies of 2 commercial phytases, a Buttiauxella sp. phytase (BSP) and a Citrobacter braakii phytase (CBP) at 500 and 1,000 FTU/kg, were studied on IP6–3 concentrations in the crop, proventriculus + gizzard, and distal ileum digesta, and ileal IP6 disappearance in broilers at day 22. Apparent ileal P and Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…The pattern of lower IP esters varied depending on phytase, Ca, and PP, but significant increases in IP3 and 4 were observed due to phytase inclusion. However, in another trial, IP4 was found to be most influenced by 500 or 1,000 FTU Buttiauxella phytase/kg inclusion, whereas there were no differences in ileal IP3 concentration between phytase and non-phytase treatments (Bello et al., 2016 ). In addition, no differences were found in ileal IP4 concentration between birds fed phytase ( A.niger or E. coli phytase at 500 FTU/kg) and non-phytase diets (Zeller et al., 2015 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The pattern of lower IP esters varied depending on phytase, Ca, and PP, but significant increases in IP3 and 4 were observed due to phytase inclusion. However, in another trial, IP4 was found to be most influenced by 500 or 1,000 FTU Buttiauxella phytase/kg inclusion, whereas there were no differences in ileal IP3 concentration between phytase and non-phytase treatments (Bello et al., 2016 ). In addition, no differences were found in ileal IP4 concentration between birds fed phytase ( A.niger or E. coli phytase at 500 FTU/kg) and non-phytase diets (Zeller et al., 2015 ).…”
Section: Discussionmentioning
confidence: 97%
“…Even though in birds fed high PP diets (0.34%) there was more IP5 remaining in both the crop and Prov+Giz, a similar pattern of increases in IP3 concentration was seen at both PP. However, recent (Menezes-Blackburn et al., 2015 ) in vivo (Walk et al., 2014 ; Bello et al., 2016 ) studies showed IP ester production may be different among phytases. For example, Walk et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2020b) . The breaking strength of the tibias was measured by the 3-point bending test using an Instron Universal Testing Instrument, as described by Bello et al. (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…Their efficacy has been clearly demonstrated (see, e.g., reviews by Selle and Ravindran, 2007 ; Dersjant-Li et al., 2015 ; Abd El-Hack et al., 2018 ) and they are commonly used in animal diets. Studies have revealed complex physical and chemical relationships occur in the gastrointestinal tract ( GIT ) between phytate, phytase, minerals, and other nutrients ( Ravindran et al., 2008 ; Amerah et al., 2014 ; Li et al., 2016 ; Sommerfeld et al., 2018 ; Bello et al., 2019 ). These must be taken into account when formulating diets with phytase to achieve maximum efficacy while maintaining nutritional balance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a current generation 6-phytase derived from Buttiauxella sp. and dosed at 1000 FTU/kg can achieve 76–92 % ileal phytate degradation in broilers [ [12] , [13] , [14] ] and 76 % ileal phytate degradation in pigs [ 15 ]. Nevertheless, new phytases with further enhanced activity and more desirable biochemical and thermal properties continue to be sought.…”
Section: Introductionmentioning
confidence: 99%